Synthesis, characterization, crystal structure, and antimicrobial studies of 2-morpholinoethyl-substituted benzimidazolium salts and their silver(I)-N-heterocyclic carbene complexes - Yildirim, Isil; Aktas, Aydin; Celepci, Duygu Barut; Kirbag, Sevda; Kutlu, Turkan; Gok, Yetkin; Aygun, Muhittin (Springer, 2017)
This article describes synthesis of N-morpholinoethylbenzimidazole (1), 2-morpholinoethyl-substituted benzimidazolium salts (NHC precursors, 2a-c), and their Ag(I) N-heterocyclic carbene (NHC) complexes (3a-c). All compounds were characterized by H-1 and C-13 Nuclear Magnetic Resonance (NMR), Fourier Transform Infrared Spectroscopy (FTIR), and elemental analysis, and their antimicrobial effects examined. The molecular structure of the NHC precursor 2a (1) was established by single-crystal X-ray diffraction analysis. Minimum Inhibition Concentration (MIC) values were determined to evaluate their antimicrobial activity against Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus bacterial strains and Candida albicans fungal species. All tested samples were compared with silver nitrate. All the compounds exhibited strong antimicrobial activity.
Keywords: N-Heterocyclic carbene; Ag-NHC complexes; Morpholine; Antimicrobial activity; Antibiotic